The Construction of Community Knowledge into Scientific Knowledge in the Banyumulek Pottery Ecotourism Area - Prelia Dwi Amanah; Nurhidayat Martin; Yayuk Andayani (Indonesian Journal of Applied Science and Technology, 2025)
Banyumulek Village in West Lombok, West Nusa Tenggara, is an ecotourism area based on pottery crafts that integrates cultural preservation, utilization of local natural resources, and community economic empowerment. This study aims to construct the community’s knowledge of the pottery-making process into scientific concepts and to identify its potential as an ethnoscience-based science learning resource. A qualitative descriptive approach was employed through field observations, in-depth interviews with artisans and collectors, and questionnaires administered to teachers and students. The research instruments were validated by experts, and data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that each stage of pottery production (from raw material collection, clay processing, shaping, drying, firing, to coloring) embodies scientific principles, including physical and chemical properties of materials, force and motion, heat transfer, and physical and chemical changes. These findings demonstrate that the traditional practices of the Banyumulek community are strongly aligned with scientific concepts. This study contributes to the development of ethnoscience studies and provides an empirical basis for designing contextual and local-wisdom-based science learning resources.